Induction of diabetes with signs of autoimmunity in primates by the injection of multiple-low-dose streptozotocin - Wei, L.; Lu, Y.; He, S.; Jin, X.; Zeng, L.; Zhang, S.; Chen, Younan; Tian, B.; Mai, G.; Yang, G.; Zhang, J.; Wang, L.; et al. (2011)
Aim: To develop a preclinical large animal model of autoimmune diabetes to facilitate the translational research of autoimmune diabetes in human. Materials and methods: Nine young rhesus monkeys received multiple-low-dose (MLD) intravenous injections of streptozotocin for five consecutive days, followed by two additional boosting injections of STZ given 1. week apart. The induction of autoimmune diabetes was evaluated by regular metabolic testing, serological assessment of islet-reactive autoantibodies and histological examination of pancreatic tissues. Results: Seven of nine treated animals became diabetic with moderate hyperglycemia initially and more severe hyperglycemia thereafter. All diabetic animals exhibited severely impaired glucose tolerance, limited islet function, and required insulin therapy to maintain relatively normal glucose metabolism and healthy status. Serological tests showed that all diabetic monkeys developed autoantibodies specifically against insulin and islet antigens. Furthermore, histological examination of the pancreata from diabetic animals revealed evidence of specific destruction of islet ß cells and islets infiltrated with T lymphocytes. Overt and persistent diabetes can be induced in young rhesus monkeys by the injection of MLD-STZ, and autoimmune responses to pancreatic islet cells seem to be involved in the development of glucose intolerance and diabetes. Conclusion: These data indicate for the first time that autoimmune diabetes can be induced in primates; this may serve as a valuable preclinical model for studying the pathogenesis of and potential therapies for autoimmune diabetes in humans. © 2011 Elsevier Inc.